A Coordinate Wise Variational Method with Tolerance Functions - Salahuddin (Journal of Applied Nonlinear Dynamics, 2026)
In this work, we use the coordinate wise variational method for optimal resource allocation problems with involve simplex type constraints. It consists in making coordinate wise steps together with special threshold control and tolerance whose values reduce sequentially, and we establish the convergence rate under mild conditions.